A Small Molecule Inhibitor of Polycomb Repressive Complex 1 Inhibits Ubiquitin Signaling at DNA Double-strand Breaks - Ismail, Ismail Hassan (American Society for Biochemistry and Molecular Biology, 2013)
Polycomb-repressive complex 1 (PRC1)-mediated histone ubiquitylation plays an important role in aberrant gene silencing in human cancers and is a potential target for cancer therapy. Here we show that 2-pyridine-3-yl-methylene-indan-1,3-dione (PRT4165) is a potent inhibitor of PRC1-mediated H2A ubiquitylation in vivo and in vitro. The drug also inhibits the accumulation of all detectable ubiquitin at sites of DNA double-strand breaks (DSBs), the retention of several DNA damage response proteins in foci that form around DSBs, and the repair of the DSBs. In vitro E3 ubiquitin ligase activity assays revealed that PRT4165 inhibits both RNF2 and RING 1A, which are partially redundant paralogues that together account for the E3 ubiquitin ligase activity found in PRC1 complexes, but not RNF8 nor RNF168. Because ubiquitylation is completely inhibited despite the efficient recruitment of RNF8 to DSBs, our results suggest that PRC1-mediated monoubiquitylation is required for subsequent RNF8- and/or RNF168-mediated polyubiquitylation. Our results demonstrate the unique feature of PRT4165 as a novel chromatin-remodeling compound and provide a new tool for the inhibition of ubiquitylation signaling at DNA double-strand breaks.